2020
DOI: 10.3390/genes11070798
|View full text |Cite
|
Sign up to set email alerts
|

Summary of BARD1 Mutations and Precise Estimation of Breast and Ovarian Cancer Risks Associated with the Mutations

Abstract: Over the last two decades, numerous BARD1 mutations/pathogenic variants (PVs) have been found in patients with breast cancer (BC) and ovarian cancer (OC). However, their role in BC and OC susceptibility remains controversial, and strong evidence-based guidelines for carriers are not yet available. Herein, we present a comprehensive catalog of BARD1 PVs identified in large cumulative cohorts of ~48,700 BC and ~20,800 OC cases (retrieved from 123 studies examining the whole coding sequence of BARD1). Using these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 151 publications
0
17
0
Order By: Relevance
“…Contrarily, the analysis of 3261 epithelial OC cases by Ramus et al and 6294 OC cases by Lilyquist et al resulted in non-significant associations of deleterious BARD1 variants with OC risk [17,19]. The meta-analysis by Suszynska and Kozlowski could not detect an association of BARD1 with OC risk in a cumulative set of~20,800 OC cases either [30].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Contrarily, the analysis of 3261 epithelial OC cases by Ramus et al and 6294 OC cases by Lilyquist et al resulted in non-significant associations of deleterious BARD1 variants with OC risk [17,19]. The meta-analysis by Suszynska and Kozlowski could not detect an association of BARD1 with OC risk in a cumulative set of~20,800 OC cases either [30].…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, Slavin et al reported an OR = 3.18 (CI = 1.34-7.36; p = 0.012) [10] and Weber-Lassalle et al reported an OR = 5.35 (CI = 3.17-9.04; p < 0.00001) [11] in 2134 and 4469 familial BC patients, respectively. Besides, a recent meta-analysis by Suszynska and Kozlowski collected data from a total of 123 published studies and consistently reported an OR = 2.90 (CI = 2.25-3.75; p < 0.0001) over a cumulative cohort of~48,700 BC patients [30]. However, there are some studies that failed to identify a significant association with BC risk, such as those published by Castéra et al and Lu et al [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…The BARD1 and BRCA1 proteins form a heterodimer complex. The interaction between the two proteins is essential for maintaining the stabilization of BRCA1 [ 14 , 19 , 20 , 21 ]. The BRCA1/BARD1 heterodimer acts in the DNA damage response signaling pathway, cell cycle control, hormone signaling modulation and chromatin structural maintenance [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, little is known about cancer susceptibility in carriers of BARD1 mutations. The most commonly studied is the association between BARD1 and breast cancer [ 19 , 20 , 27 ]. Most recent, large association analysis of approximately 110,000 women performed by Breast Cancer Association Consortium provided evidence of an association between truncating BARD1 mutation and an elevated risk of breast cancer [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation